CO TRAPIŁO GRECKICH ŻOŁNIERZY? ŻOŁNIERSKIE BOLĄCZKI W ŚWIETLE GRECKIEJ HISTORIOGRAFII OKRESU KLASYCZNEGO - Kostuch, Lucyna (Studia Europaea Gnesnensia, 2017)
The aim of the paper is to compile a list of typical complaints that a Greek soldier of the Classical period might have had. For that purpose, the author analyses the great war narratives of that time: Histories by Herodotus, History of the Peloponnesian War by Thucydides Xenophon’s Hellenica, Anabasis, and Agesilaus.